Study on Deformation Mechanism and Supporting Countermeasures of Compound Roofs in Loose and Weak Coal Roadways. (12th November 2020) - Cui, Jianfeng; Wang, Weijun; Yuan, Chao; Cao, Liming; Guo, Yuning; Fan, Lei
Abstract : This paper considers the 333 return airway of the Gaokeng Coal Mine to analyze the deformation characteristics and failure mechanism of the surrounding rock of the composite roof for a loose and weak coal roadway. The reasons for the large deformation are explored and the superiority of the prestressed truss and anchor rope is compared to ordinary anchor cables from the perspective of mechanics to propose a targeted coal roadway support method. Sinking of the composite roof in the coal roadway is accompanied with a release and transfer of the surrounding rock stress. The pressure of the composite roof transfers to the roadway sides and intensifies the fracture process of the coal body. As a result, the ability to support the composite roof is weakened, and it further bends and sinks to form a vicious cycle that repeats itself. Therefore, the support of the composite roof in the coal roadway should consider the roof, roadway sides, and floor as a single unit to achieve the support goal of reinforcing the roadway sides and roof. Based on the above analysis, a comprehensive control technology with a truss and anchor rope is proposed as the main body and a bolt + anchor cable + metal network as the auxiliary. This technology can improve the integral bearing capacity of the composite roof, strengthen the roadway side structures, and reinforce the roadway sides and roof. Numerical simulation and field application results show that the support scheme can effectively realize safe control of the composite roof in coal roadways.